(Not so) voluntary hospitalization as part of Zolpidem-induced complex sleep behaviour: a case report - Sriraksha R Nayak; Suman S Rao; Karthik K N; Harsha G T; Narayana Keertish (BMC Psychiatry)
Abstract Background Since its approval 26 years ago, Zolpidem has been implicated in 61 cases of complex sleep behaviours (CSBs) reported to the US FDA. These cases typically describe activities such as eating, walking, cooking or driving while asleep after Zolpidem use. This report describes a unique presentation of Zolpidem-induced CSB. Case presentation A 44-year-old male with recurrent depressive disorder presented with a history of waking up in a hospital with no recollection of how he was admitted. He subsequently discharged himself against medical advice. In addition to his regular treatment, he had been prescribed Zolpidem on an as-needed basis for persistent insomnia. A thorough review of his past medical history with corresponding prescriptions revealed two similar instances in which he sought discharge against medical advice after waking up in a hospital with no recollection of how he was admitted. Each instance was temporally correlated with the use of Zolpidem. Conclusions This case illustrates a rare presentation of Zolpidem-induced CSB, where the patient hired a cab to a psychiatric hospital, admitted himself and cooperated with inpatient management until regaining awareness the following morning. The patient experienced three similar episodes of Zolpidem-induced CSB, each resulting in voluntary psychiatric admission. Practitioners prescribing Z-drugs, either alone or in combination with other psychotropic medications, should be aware of these rare yet potentially serious adverse events and their forensic implications.